What is the role of endoscopic retrograde cholangiopancreatography in assessing traumatic rupture of the pancreatic in children?. (1st February 2016) - Keil, Radan; Drabek, Jiri; Lochmannova, Jindra; Stovicek, Jan; Rygl, Michal; Snajdauf, Jiri; Hlava, Stepan
Abstract: Background and study aims: Trauma is one of the most common causes of morbidity and mortality in the pediatric population. The diagnosis of pancreatic injury is based on clinical presentation, laboratory and imaging findings, and endoscopic methods. CT scanning is considered the gold standard for diagnosing pancreatic trauma in children. Patients and methods: This retrospective study evaluates data from 25 pediatric patients admitted to the University Hospital Motol, Prague, with blunt pancreatic trauma between January 1999 and June 2013. Results: The exact grade of injury was determined by CT scans in 11 patients (47.8%). All 25 children underwent endoscopic retrograde cholangiopancreatography (ERCP). Distal pancreatic duct injury (grade III) was found in 13 patients (52%). Proximal pancreatic duct injury (grade IV) was found in four patients (16 %). Major contusion without duct injury (grade IIB) was found in six patients (24%). One patient experienced duodeno-gastric abruption not diagnosed on the CT scan. The diagnosis was made endoscopically during ERCP. Grade IIB pancreatic injury was found in this patient. One patient (4%) with pancreatic pseudocyst had a major contusion of pancreas without duct injury (grade IIA). Four patients (16%) with grade IIB, III and IV pancreatic injury were treated exclusively and nonoperatively with a pancreatic stent insertion and somatostatine. Two patients (8%) with a grade IIB injury were treated conservatively only with somatostatine without drainage. Eighteen (72 %) children underwent surgical intervention within 24 h after ERCP. Conclusion: ERCP is helpful when there is suspicion of pancreatic duct injury in order to exclude ductal leakage and the possibility of therapeutic intervention. ERCP can speed up diagnosis of higher grade of pancreatic injuries.